2022
DOI: 10.1002/cpdd.1168
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics, Bioavailability, and Swallowing Safety With Riluzole Oral Film

Abstract: Dysphagia is highly prevalent in patients with amyotrophic lateral sclerosis (ALS). Riluzole is a US Food and Drug Administration-approved treatment for ALS. Riluzole oral film (ROF; Exservan TM ) contains riluzole in a polymer-based film matrix. The ROF is administered by placing on the tongue, where it dissolves and the drug is ingested with the saliva. Two clinical trials assessed the safety and tolerability of the ROF. Bioavailability and pharmacokinetics (PK) were evaluated in an open-label, randomized, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…Moreover, it can be easily applied by different patients as well as those who cannot easily access water (8,9). Several studies have confirmed the bioequivalence between OSF and the reference formulations (e.g., sildenafil, clobazam, riluzole, and midazolam) (10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it can be easily applied by different patients as well as those who cannot easily access water (8,9). Several studies have confirmed the bioequivalence between OSF and the reference formulations (e.g., sildenafil, clobazam, riluzole, and midazolam) (10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, as the disease progresses, swallowing difficulties may gradually appear in ALS patients, resulting in an inability to take oral riluzole tablets. Therefore, in recent years, researchers have devoted themselves to the development of new dosage forms of riluzole, such as suspension and oral films ( Wymer et al, 2023 ). The simple method was established for the determination of riluzole concentration, which was convenient for other groups to refer to, and can be applied in the study of pharmacokinetics and bioavailability of new forms of riluzole.…”
Section: Resultsmentioning
confidence: 99%
“…*When configuring whole blood stable QC samples, assuming that riluzole is not distributed in blood cells, the volume of plasma centrifuged is about half of the volume of whole blood, so the configured final concentrations of whole blood QC samples were 7.5, 30, and 300 ng/mL. Frontiers in Pharmacology frontiersin.org devoted themselves to the development of new dosage forms of riluzole, such as suspension and oral films (Wymer et al, 2023). The simple method was established for the determination of riluzole concentration, which was convenient for other groups to refer to, and can be applied in the study of pharmacokinetics and bioavailability of new forms of riluzole.…”
Section: Applicationmentioning
confidence: 99%
“…The Riluzole drug was first developed as an oral tablet of 50 mg taken twice a day but given the fact that many ALS patients are struggling with dysphagia, the development of a bioequivalent oral suspension of Riluzole (5 mg/mL) was essential [34,35]. Furthermore, recently, an oral-film formulation form of Riluzole has been developed that poses another option to simplify administration and ensure the continuation of medical treatment [36,37].…”
Section: Medical Treatment 211 Riluzolementioning
confidence: 99%